Electronic control unit development and emissions evaluation for hydrogen diesel dual-fuel engines - Karagoz, Yasin; Sadeghi, Majid Mohammad (SAGE PUBLICATIONS LTD, 2018)
In this study, it was aimed to operate today's compression ignition engines easily in dual-fuel mode with a developed electronic control unit. Especially, diesel engines with mechanical fuel system can be easily converted to common-rail fuel system with a developed electronic control unit. Also, with this developed electronic control unit, old technology compression ignition engines can be turned into dual-fuel mode easily. Thus, thanks to the flexibility of engine maps to be loaded into the electronic control unit, diesel engines can conveniently be operated with alternative gas fuels and diesel dual fuel. In particular, hydrogen, an alternative, environmentally friendly, and clean gas fuel, can easily be used with diesel engines by pilot spraying. Software and hardware development of electronic control unit are made, in order to operate a diesel engine with diesel T hydrogen dual fuel. Finally, developed electronic control unit was reviewed on 1500 r/min stable engine speed on different hydrogen energy rates (0%, 15%, 30%, and 45% hydrogen) according to thermic efficiency and emissions (CO, total unburned hydrocarbons, NOx, and smoke), and apart from NO(x )emissions, a significant improvement has been obtained. There was no increased NOx emission on 15% hydrogen working condition; however, on 45% hydrogen working condition, a dramatic increase arose.
Keywords: Electronic control unit; engine control strategy; emissions; dual fuel; alternative fuel; SPARK-IGNITION ENGINE; COMBUSTION CHARACTERISTICS; PERFORMANCE; GAS; INJECTION; GASOLINE; PRESSURE; ETHANOL; SPEED; Thermodynamics; Engineering